2004
DOI: 10.1530/eje.0.151u039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic defects in congenital hypothyroidism

Abstract: Recently molecular genetic defects in some cases of congenital hypothyroidism (CH) as well as of rare cases of central hypothyroidism have been identified. These studies have led to the description of so far unexplained forms of these disorders. In some patients with CH early diagnosis by newborn screening and early treatment was not able to lead to a normal mental development. This could subsequently be explained by molecular defects of transcription factors (FOXE-1/FKHL15, NKX2.1) which are important not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 36 publications
1
28
0
4
Order By: Relevance
“…62 In dyshormonogenesis, concentrations of serum Tg can be low if there is a defect in Tg synthesis or intracellular processing or high if the defect is in other pathways. In an early study of congenital hypothyroidism, no significant differences in serum Tg were found between neonates with thyroid aplasia confirmed by thyroid scintigraphy (range ¼ 15-290 mg/L) and a control group of euthyroid neonates (range ¼ 34-700 mg/L).…”
Section: Other Indications For the Measurement Of Serum Tgmentioning
confidence: 99%
“…62 In dyshormonogenesis, concentrations of serum Tg can be low if there is a defect in Tg synthesis or intracellular processing or high if the defect is in other pathways. In an early study of congenital hypothyroidism, no significant differences in serum Tg were found between neonates with thyroid aplasia confirmed by thyroid scintigraphy (range ¼ 15-290 mg/L) and a control group of euthyroid neonates (range ¼ 34-700 mg/L).…”
Section: Other Indications For the Measurement Of Serum Tgmentioning
confidence: 99%
“…Murine Nkx2.5 is expressed in early heart progenitor cells, as well as in thyroid, tongue, stomach and spleen (3,6,7). The NKX2.5 transcription factor is known to be essential for normal heart morphogenesis, myogenesis and function (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we review interspecies, racial, geographical, and interindividual variation in the thyroid hormone pathways in humans and other animals. The present review focuses on natural and subclinical variation in thyroid hormone physiology and will not cover the genetic basis for congenital hypothyroidism [1,2,3,4,5], congenital hyperthyroidism [6,7], autoimmune diseases [8], and thyroid cancers [9], for which a number of good review articles are already available.…”
Section: Introductionmentioning
confidence: 99%